Global, regional and national trends of atmospheric ammonia derived from a decadal (2008–2018) satellite record. (6th May 2021) - Van Damme, Martin; Clarisse, Lieven; Franco, Bruno; Sutton, Mark A; Erisman, Jan Willem; Wichink Kruit, Roy; van Zanten, Margreet; Whitburn, Simon; Hadji-Lazaro, Juliette; Hurtmans, Daniel; Clerbaux, Cathy; Coheur, Pierre-François
Abstract: Excess atmospheric ammonia (NH3 ) leads to deleterious effects on biodiversity, ecosystems, air quality and health, and it is therefore essential to monitor its budget and temporal evolution. Hyperspectral infrared satellite sounders provide daily NH3 observations at global scale for over a decade. Here we use the version 3 of the Infrared Atmospheric Sounding Interferometer (IASI) NH3 dataset to derive global, regional and national trends from 2008 to 2018. We find a worldwide increase of 12.8 ± 1.3 % over this 11-year period, driven by large increases in east Asia (5.80 ± 0.61% increase per year), western and central Africa (2.58 ± 0.23 % yr −1 ), North America (2.40 ± 0.45 % yr −1 ) and western and southern Europe (1.90 ± 0.43 % yr −1 ). These are also seen in the Indo-Gangetic Plain, while the southwestern part of India exhibits decreasing trends. Reported national trends are analyzed in the light of changing anthropogenic and pyrogenic NH3 emissions, meteorological conditions and the impact of sulfur and nitrogen oxides emissions, which alter the atmospheric lifetime of NH3 . We end with a short case study dedicated to the Netherlands and the 'Dutch Nitrogen crisis' of 2019.